Validation of a Precise Impactor in a Rodent Cervical Spinal Cord Injury Hemi-Contusion Model - Jose A. Castillo; Michael Nhien Le; Christopher Pivetti; Jordan E. Jackson; Edwin Kulubya; Zachary Paxton; Camille Reed; Khadija Soufi; Arash Ghaffari Rafi; Allan Martin; Richard Price; Kee Kim; et al. (BioMed)
Background: Cervical spinal cord injuries (SCIs) are the most common type of human SCI. Although various animal SCI contusion models have been developed to mirror human pathology, few have described cervical-level injuries. This study aims to validate and establish optimal impact parameters to produce consistent incomplete cervical SCIs for testing novel therapies. Methods: Using a precise impactor, 3 cervical spinal cord hemi-contusions of varying severities were induced by modifying penetration depths and controlling dwell times. Penetration depths of 2.11 mm (n = 4), 2.24 mm (n = 4), and 2.36 mm (n = 3) were used with a dwell time of 0.05 s to create mild, moderate, and severe injuries. Behavioral assessments in weeks 1, 2, 5, and 8 included grooming test, forelimb asymmetry test, and the Irvine, Beatties, and Bresnahan forelimb scale (IBB). After 8 weeks, rats were euthanized, and spinal cord histology was performed. Results: Within each group, animals exhibited consistent motor deficits and functional recovery. Mean IBB scores varied significantly between each group at week 8 (p < 0.0001). Ipsilateral forelimb usage significantly improved throughout the study period in the mild (2.11 mm) and moderate (2.24 mm) groups, while the severely (2.36 mm) injured group continued to exhibit 100% asymmetrical forelimb usage. Conclusions: This study demonstrates that a precise impactor can create reproducible models of incomplete cervical SCIs. A penetration depth of 2.24 mm resulted in moderate injury with significant motor deficits that slowly improved over time, permitting future therapeutic studies in functional recovery.